System in package module and manufacturing method thereof - HSIEH, CHING-FENG; CHEN, CHI-SHENG (2013)
A system in package module and a manufacturing method thereof are provided. A substrate with circuit layers, bonding pads and dielectric layers is provided, and scribing lines are formed on the substrate. Ground buried vias corresponding to the scribing lines are formed in at least one dielectric layer and the circuit layers adjacent to the dielectric layer, and an electric component is provided on the substrate. Then, an encapsulation gel covering the electric component is formed on the substrate. After that, the substrate is cut along the scribing lines in order to expose the ground buried vias. Finally, a shielding layer is formed on the encapsulation gel and the side walls of the substrate to obtain each of the system in package modules. Therefore, the present invention prevents interference of electromagnetic radiation, and occupies less space of the top surface and the bottom surface of the substrate.